CODE-MIXING IN MERRY RIANA AND REZA RAHADIAN’S YOUTUBE DISCOURSE - Tri Ayu Aprillia; Rika Ningsih (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates code-mixing practices in the YouTube discourse of Merry Riana and Reza Rahadian, particularly in the episode “Speaking Out About Politics, Family, and Identity.” Drawing on Suandi’s sociolinguistic framework, the study examines the types of code-mixing and the factors influencing their occurrence in digital communication. Using a qualitative content analysis approach, the data were collected through transcription, observation, and note-taking techniques from a podcast video uploaded on YouTube. The findings reveal 287 instances of code-mixing consisting of clause-level (155), word-level (75), and phrase-level (57) insertions, with clause-level code-mixing appearing most frequently. All identified forms are categorized as outward code-mixing due to the insertion of English elements into Indonesian discourse. The dominant influencing factors include the use of popular terms, bilingual identity, communicative efficiency, and speakers’ linguistic habits. The study demonstrates that code-mixing functions not only as a linguistic phenomenon but also as a strategic communicative practice for constructing professional identity and audience engagement in digital media discourse.